Social, Human Capital and Innovation: An Exploratory Study of European Atlantic Organisations - Almeida, Maria Helena (Advances in Social Sciences Research Journal, 2014)
At European Union level, territorial cooperation initiatives are aligned with operational programs focused in innovation as a policy target for socioeconomic development. The project HARVEST Atlantic is a project developed under the Atlantic Area Programme that intends to identify and exchange good practices and sustainable solutions based on innovation for the maritime and marine economy. Based in a transnational survey applied in Portugal, Spain, Scotland and Ireland, with a sample of 243 organisations, this article was structured in two empirical components. The first component, using the SPSS - Statistical Package for the Social Sciences (version 21.0), focused the descriptive analysis of selected key dimensions of the survey. A second component used structural equation model techniques (software AMOS program GRAPHICS) to create a model relating innovation with social (relational) capital and human capital. Results show differences between the four countries of North Atlantic in the impact that innovation activities have had on organizational behaviour in the period 2011-2012. We validated the model in which relational capital and human capital are significant for the impacts generated by innovation activities (and consequent improvements in the performance of organisations).